THE EFFECTIVENESS OF USING INTERPALS TO SUPPORT STUDENTS IN THEIR LANGUAGE LEARNING - Sudirman; M. Ferdinansyah; Muhammad Ridwansyah; Edison Parlindungan; Arifin Setiabudi (ASIAN PUBLISHER, 2025)
The study is aimed at finding insights into the effectiveness of using Interpals as a language learning tool and inform educators on how to better support students in their language learning activities. The methodology to collect data is study literature reviews on the topic. By gathering information from multiple sources, the research aims to provide a comprehensive understanding of the role of Interpals in language learning and its potential impact on students' linguistic and cultural development. Interpals provides a unique and valuable opportunity for language learners to practice and improve their language skills through interactions with native speakers. By actively engaging with users from different cultural backgrounds and utilizing the language exchange features on the platform, users can enhance their language learning experience and gain a deeper understanding of different cultures. Through consistent practice and meaningful conversations with native speakers, users can improve their language skills and build lasting connections with individuals from around the world. By immersing themselves in authentic language exchanges, users can gain insight into different perspectives and broaden their cultural knowledge. Ultimately, Interpals offers a unique opportunity for language learners to not only improve their language proficiency but also foster meaningful cross-cultural relationships.